Historical Fires Induced Deforestation in Relict Scots Pine Forests during the Late 19th Century - J. Julio Camarero; Gabriel Sangüesa-Barreda; Cristina Montiel-Molina; Reyes Luelmo-Lautenschlaeger; Paula Ortega; Mar Génova; José Antonio López-Sáez (Fire, 2021)
Mountain forests are subjected to several pressures including historical land-use changes and climate warming which may lead to shifts in wildfire severity negatively impacting tree species with low post-fire growth resilience. This is the case of relict Mediterranean Scots pine (Pinus sylvestris) forests in the Sierra de Gredos mountains (central Spain). We reconstructed the historical fire regime of these forests since 1700 by using paleoecology, historical ecology and dendroecology. We detected an increase in charcoal accumulation rate and coprophilous fungi in peat bogs during the late 19th century when the pine pollen percentage sharply decreased, historical records of fire peaked and many trees showed growth suppressions. We inferred an increased wildfire incidence during the late 19th century, which could have shaped the current distribution of Scots pine forests. This shift in fire-forest interactions can be explained by the uncontrolled use of mountain forests and grasslands due to the dissolution of “Mesta”, one of the major and lasting transhumance livestock associations in Europe. Integrating historical human and climate influences on fire regimes allows decomposing the resilience and conservation components of relict forests.